Pancasila and Islamic Religious Education as Ethical Foundations: Developing Digital Law in the Era of Technological Transformation through Islamic Sociological Jurisprudence Theory - Ahmad Muhammad Musain Nasoha; Afifah Nur Khusna; Erma Nur Fitriyani; Yesha Renata Andyne Ramadhani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the integration of Pancasila values and Islamic Religious Education (PAI) in shaping digital ethics and to examine the development of digital law through the Islamic Sociological Jurisprudence Theory approach. This research employs a qualitative method with a literature study approach based on relevant academic sources and journals. The findings indicate that the integration of Pancasila and PAI serves as a comprehensive ethical foundation in shaping digital behavior by reinforcing moral, spiritual, and social values. Furthermore, digital law is understood as a product of the interaction between social and religious values, which is dynamic and adaptive to technological developments. The Islamic Sociological Jurisprudence Theory contributes to constructing a legal paradigm that is not only formal-legal but also contextual and oriented toward public welfare (maslahah). The ethical-based digital law development model integrating Pancasila and Islamic values is considered relevant in addressing contemporary digital challenges, such as misinformation, privacy violations, and cybercrime. However, this study also identifies limitations, particularly in the implementation aspect, which remains largely normative and has not been optimally integrated into concrete policies. Therefore, it is necessary to strengthen adaptive regulations, develop applicable digital ethics education, and conduct further empirical research to establish a just and sustainable digital legal system.